1976
DOI: 10.1063/1.432402
|View full text |Cite
|
Sign up to set email alerts
|

CI study of the water dimer potential surface

Abstract: The potential energies for the water dimer in various geometrical configurations have been calculated with a configuration–interaction method. The computed dimerization binding energies corresponding to the potential minima for the linear, cyclic, and bifurcated configurations are −5.6, −4.9, and −4.2 kcal/mol, respectively; the correlation effects account for −1.1, −1.2, and −0.9 kcal/mol, respectively, of the total binding energy for these three dimeric forms. The correlation effects for the entire potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
370
3
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,189 publications
(388 citation statements)
references
References 16 publications
12
370
3
2
Order By: Relevance
“…18), have a larger quadrupole because the negative charge is moved from the oxygen to a site near the center of mass as in the MCY model (Ref. 19). The two new TIP4P-type models differ slightly from TIP4P in the partial charges and the negative charge location and give excellent properties for pure water over a large range of temperatures although the dielectric constant is somewhat low.…”
Section: Introductionmentioning
confidence: 99%
“…18), have a larger quadrupole because the negative charge is moved from the oxygen to a site near the center of mass as in the MCY model (Ref. 19). The two new TIP4P-type models differ slightly from TIP4P in the partial charges and the negative charge location and give excellent properties for pure water over a large range of temperatures although the dielectric constant is somewhat low.…”
Section: Introductionmentioning
confidence: 99%
“…39 Ab initio calculations on the ͓Cr͑H 2 O͒ 6 ͔ ϩ3 ͑H 2 O͒ 12 cluster showed that almost half of the overestimation ͑about 65 kcal/mol͒ is due to the many-body effects present in the second hydration shell. In the simulations performed for this cation, water-water interactions were described by nonpolarizable water models: MCY 48 and TIP4P. 49 In principle, a realistic potential should be able to accurately reproduce all the properties of the system being simulated; the validation against the available experimental data is a requirement to assess the reliability of the model in describing properties that have not been determined experimentally, and in providing an explanation in terms of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…2 The MCY potential is a site-site form including Coulomb terms and double exponential terms fitted to 66 configuration interaction dimer energies. This form was quite successful at predicting observables despite the very small number of grid points and, from the current perspective, rather inaccurate values of ab initio computed energies.…”
Section: Introductionmentioning
confidence: 99%